2011
DOI: 10.1007/s10801-011-0317-1
|View full text |Cite
|
Sign up to set email alerts
|

A simple bijection between standard 3×n tableaux and irreducible webs for $\mathfrak{sl}_{3}$

Abstract: Combinatorial spiders are a model for the invariant space of the tensor product of representations. The basic objects, webs, are certain directed planar graphs with boundary; algebraic operations on representations correspond to graph-theoretic operations on webs. Kuperberg developed spiders for rank 2 Lie algebras and sl 2 . Building on a result of Kuperberg, Khovanov-Kuperberg found a recursive algorithm giving a bijection between standard Young tableaux of shape 3 × n and irreducible webs for sl 3 whose bou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 8 publications
1
35
0
Order By: Relevance
“…Kuperberg [42] showed that web invariants are a basis for C[Gr(3, m)], and with Khovanov [41] gave a bijective labeling T → [W (T )] of these webs by tableaux T ∈ SSYT (3, [m]). For an easily computable description of this bijection we refer to [62]. One useful property of the bijection is the following: if T has an i weakly northeast of an i + 1, then boundary vertices i, i + 1 are joined by a "fork" or "Y" in W (T ) (see Example 6.4 for an illustration of the meaning of "fork").…”
Section: Fomin and Pylyavskyy's Conjecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…Kuperberg [42] showed that web invariants are a basis for C[Gr(3, m)], and with Khovanov [41] gave a bijective labeling T → [W (T )] of these webs by tableaux T ∈ SSYT (3, [m]). For an easily computable description of this bijection we refer to [62]. One useful property of the bijection is the following: if T has an i weakly northeast of an i + 1, then boundary vertices i, i + 1 are joined by a "fork" or "Y" in W (T ) (see Example 6.4 for an illustration of the meaning of "fork").…”
Section: Fomin and Pylyavskyy's Conjecturesmentioning
confidence: 99%
“…The second line is its homogeneous lift ch(T ) ∈ C[Gr (3,6)] expressed in the basis of standard monomials. This element of C[Gr (3,6)] is a web invariant with diagram , and this web is labeled by T in the Khovanov-Kuperberg bijection (see e.g [62,Section 3.2]). This is one of the two non-Plücker cluster variables in C[Gr (3,6)] (it is Y 123456 in the notation of [58]).…”
mentioning
confidence: 99%
“…Our second observation is as follows. When r = 2 or 3, there is a well-known bijection between standard young tableaux and non-elliptic webs, due to Khovanov and Kuperberg [5] (see also [18]). It has the property that rotation of webs is given by promotion of standard young tableaux, and this can be used to give an elementary proof [15] of the cyclic sieving phenomenon for rectangular tableaux with 2 or 3 or rows.…”
Section: Appendix: Web Duality Picturesmentioning
confidence: 99%
“…and resolving according to standard knot-theoretic relations. In this paper, as in much other combinatorial work [29,34], we focus on webs for (V + ) ⊗3n .…”
Section: Introductionmentioning
confidence: 99%